Heat-stabilized conductive polymer coating

JP2024508584A5Pending Publication Date: 2024-12-16COMMONWEALTH SCI & IND RES ORG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023537661
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-21
Filing Date
2021-12-21
Publication Date
2024-12-16

AI Technical Summary

Technical Problem

Conductive polymers, particularly polyaniline, suffer from limited thermal stability, which hinders their application in high-temperature environments, and existing solutions often compromise processability or conductivity.

Method used

Incorporating alkali metal salts, amphoteric metal oxides, and antioxidants as thermal stabilizers into polyaniline conductive polymer compositions, allowing for improved thermal stability while maintaining electrical conductivity and processability.

Benefits of technology

The compositions exhibit enhanced thermal stability, with electrical resistance remaining below 100 MΩ for at least a week in high-temperature environments, and can be easily processed into coatings for various substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000041_0000
    Figure 00000041_0000
  • Figure 00000041_0001
    Figure 00000041_0001
  • Figure 00000041_0002
    Figure 00000041_0002
Patent Text Reader

Abstract

The present disclosure relates generally to coatings and compositions comprising conductive polymers. The present disclosure also relates to thermally stable coatings and compositions comprising solution processable polyaniline conductive polymers and thermal stabilizers, and processes for preparing the coatings and compositions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to coatings and compositions that include conductive polymers. The present disclosure also relates to thermally stabilized coatings and compositions that include solution-processable conductive polymers, and processes for preparing the coatings and compositions. [Background technology]

[0002] Conductive polymers such as polyaniline have attracted much attention in recent years as materials for a variety of applications, such as antistatic coatings and corrosion protection, among other potential uses. Currently, there is a demand for conductive polymer coatings with improved performance in a variety of applications, such as conductive polymer coatings with higher thermal stability.

[0003] As an example, the emeraldine base of non-conductive polyaniline (i.e. undoped) is thermally stable up to around 450°C, whereas the thermal stability of conductive polyaniline (i.e. doped) is significantly less. Existing techniques that can address the thermal stability of conductive polymers are limited and in some instances involve modification of the dopant, including self-doping of the polymer. The difficulty with modifying the dopant is that it may no longer form a processable solution of the conductive polymer. This significantly limits the applications of this technique.

[0004] There is a need to provide new and alternative polyaniline conductive polymer compositions, coatings, and processes to obtain the physical and / or electronic improvements in polyaniline conductive polymers brought about by the use of dopants, and to retain electrical conductivity at elevated temperatures, at least for a period of time.

[0005] Any discussion of documents, acts, materials, devices, articles or the like which has been described in the present specification is solely for the purpose of providing a context for the present disclosure and is not to be construed as an admission that any or all of such matters form part of the prior art base or were common general knowledge in the art relevant to the present disclosure as existing prior to the priority date of each claim of this application. Summary of the Invention

[0006] The present disclosure provides specific agents that are compatible with coating compositions that include polyaniline conductive polymers to improve the thermal stability of the coating. The present disclosure also provides compositions that include polyaniline conductive polymers and thermal stabilizers that are easily processable for the preparation of coatings on various substrates.

[0007] In one aspect, there is provided a composition comprising a solution processable polyaniline conductive polymer and one or more thermal stabilizers selected from an alkali metal salt, an amphoteric metal oxide, an antioxidant, or any combination thereof.

[0008] In another aspect, there is provided a composition consisting of a solution processable polyaniline conductive polymer, one or more thermal stabilizers selected from alkali metal salts, amphoteric metal oxides, antioxidants, or any combination thereof, optionally a film former, and optionally one or more additives.

[0009] In another aspect, there is provided a liquid formulation comprising a solution processable polyaniline conductive polymer in an organic solvent, one or more first heat stabilizers selected from alkali metal salts and optionally amphoteric metal oxides, and one or more second heat stabilizers selected from antioxidants, wherein the total amount (wt % of the total formulation) of the one or more first heat stabilizers is from about 2 wt % to about 7 wt %, and the total amount (wt % of the total formulation) of the first and second heat stabilizers is less than about 9 wt %, wherein the first and second heat stabilizers are present in an organic solvent, and wherein the polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent.

[0010] In another aspect, there is provided a liquid formulation consisting of a solution processable polyaniline conductive polymer in an organic solvent, one or more first heat stabilizers selected from alkali metal salts and optionally amphoteric metal oxides, one or more second heat stabilizers selected from antioxidants, and one or more film forming agents, wherein the total amount (wt % of the total formulation) of the one or more first heat stabilizers is from about 2 wt % to about 7 wt %, and the total amount (wt % of the total formulation) of the first and second heat stabilizers is less than about 9 wt %, wherein the first and second heat stabilizers are present in an organic solvent, and the polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent.

[0011] In another aspect, there is provided a method for preparing a liquid formulation comprising the step of mixing (i) one or more first thermal stabilizers selected from alkali metal salts and optionally amphoteric metal oxides, and (ii) one or more second thermal stabilizers selected from antioxidants, with (ii) a solution processable polyaniline conductive polymer dissolved in an organic solvent, wherein the polyaniline conductive polymer is an organic solvent soluble polyaniline conductive polymer salt prepared in-situ by polymerizing aniline monomers with a protonic acid in an organic solvent, wherein the total amount (wt % of the total formulation) of the one or more first thermal stabilizers is from about 2 wt % to about 7 wt %, the total amount (wt % of the total formulation) of the first and second thermal stabilizers is less than about 9 wt %, and the polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent.

[0012] In another aspect, a substrate is provided comprising one or more coating layers, at least one of the coating layers comprising a formulation according to any aspect, embodiment, or embodiment thereof described herein.

[0013] In another aspect, a coating is provided for application to an optionally coated substrate, the coating comprising a formulation according to any aspect, embodiment, or example thereof described herein.

[0014] In another aspect, there is provided a coating system comprising: (i) a substrate which may be coated; (ii) one or more optional postcoat layers; and (iii) one or more layers located between i) and (ii) comprising a formulation according to any aspect, embodiment, or example thereof described herein.

[0015] In an embodiment, the polyaniline conductive polymer coating or the use of the above method may be provided by a coating composition according to any aspect, embodiment, or example thereof described herein.

[0016] Any aspect described herein applies mutatis mutandis to every other aspect unless expressly stated otherwise.

[0017] The present disclosure is not limited by the specific embodiments described herein, which are for illustrative purposes only, and functionally equivalent products, compositions and methods are clearly within the scope of the disclosure described herein.

[0018] Throughout this specification, unless expressly stated otherwise or unless the context otherwise requires, references to a single step, composition of matter, group of steps, or group of compositions of matter are intended to include one and more than one of them (i.e., one or more).

[0019] Preferred embodiments of the present disclosure will now be further described and illustrated, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a schematic diagram of a continuous flow process for preparing a conductive polymer according to an example of the present disclosure. [Diagram 2] FIG. 1 is a flow diagram illustrating a process for preparing a heat-stabilized conductive polymer coating according to an example of the present disclosure. [Diagram 3] 1 shows photographic images of thin films formed from conductive polymer coatings containing thermal stabilizers according to some embodiments of the present disclosure. [Figure 4] 1 provides resistance measurements of PANI films containing thermal stabilizers according to several examples of the present disclosure collected with a multimeter over time during heating at 150° C. [Diagram 5] 1 provides TGA data according to several embodiments of the present disclosure. [Figure 6] 1 provides representative TGA-MS curves showing thermal desulfonation of DNNSA (m / z 64, 48, and 80) according to embodiments of the present disclosure. [Figure 7] This is the TGA-MS curve of S3 (m / z 18). [Figure 8] FIG. 1 shows the conductivity data of PANI-DNNSA films containing O2T heated under air and N2 atmosphere according to an embodiment of the present disclosure. [Figure 9] 1 illustrates the effect of curing and heating atmospheres on the subsequent thermal stability of films according to several examples of the present disclosure. [Figure 10] 1 provides a data summary based on time to failure (as determined by multimeter) according to several embodiments of the present disclosure. [Figure 11] 1 provides the change in PANI thin film breakdown time under heating with ZnO concentration according to an embodiment of the present disclosure. [Figure 12] 1 provides a graph showing continuous logging of film resistance for samples containing different amounts of silicone dispersion (R-1009) with thermal stabilizer according to some embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present disclosure describes research conducted to identify alternative and improved polyaniline conductive polymer compositions, as well as various non-limiting examples below of optional formulations, coatings, and methods of making and using the same.

[0022] General Definitions and Terminology In the following description, reference is made to the accompanying drawings, which form a part hereof, and which show, by way of example, several embodiments, It is understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure.

[0023] With respect to the definitions provided herein, unless otherwise stated or implied by the context, the defined terms and phrases include the meanings provided. Furthermore, unless otherwise expressly stated or apparent from the context, the following terms and phrases are not intended to exclude the meanings acquired by those of ordinary skill in the art. The definitions are provided to aid in the description of certain embodiments and are not intended to limit the scope of the claims. Furthermore, unless otherwise dictated by context, singular terms shall include the plural and plural terms shall include the singular.

[0024] All publications discussed and / or referenced herein are hereby incorporated by reference in their entirety.

[0025] Throughout this disclosure, unless expressly stated otherwise or unless the context otherwise requires, reference to a single step, composition of matter, group of steps, or group of compositions of matter is intended to include one and the plural (i.e., one or more) thereof. Thus, as used herein, the singular forms "a," "an," and "the" include plural aspects unless the context clearly dictates otherwise. For example, reference to "a" includes two or more as well as one; reference to "an" includes two or more as well as one; reference to "the" includes two or more as well as one, etc.

[0026] Those skilled in the art will appreciate that the disclosure herein is susceptible to variations and modifications other than those specifically described. The disclosure is to be understood to include all such variations and modifications. The disclosure also includes all examples, steps, features, methods, compositions, coatings, processes, and coated substrates referred to or shown herein, individually or collectively, and any and all combinations or any two or more of said steps or features.

[0027] The term "and / or," e.g., "X and / or Y," shall be understood to mean either "X and Y" or "X or Y," and shall be interpreted as providing explicit support for both meanings or either meaning.

[0028] Unless otherwise indicated, the terms "first," "second," and the like are used herein merely as labels and are not intended to impose any sequential, positional, or hierarchical requirements on the items they refer to. Moreover, reference to a "second" item does not require or exclude the presence of lower numbered items (e.g., the "first" item) and / or higher numbered items (e.g., the "third" item).

[0029] As used herein, the phrase "at least one of" used in conjunction with enumerated items means that various combinations of one or more of the enumerated items can be used and only one of the enumerated items may be required. An item may refer to a particular object, article, or category. In other words, "at least one of" means that any combination of items or any number of items from the enumeration may be used, but not all of the enumerated items are required. For example, "at least one of item A, item B, and item C" may mean, for example, "item A," "item A and item B," "item B," "item A, item B, and item C," or "item B and item C." In some cases, "at least one of item A, item B, and item C" may mean, for example, but not by way of limitation, "2 items A, 1 item B, and 10 items C," "4 items B, and 7 items C," or any other suitable combination.

[0030] It should be understood that certain features, which are, for clarity, described herein in the context of separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features, which are, for brevity, described in the context of a single embodiment, may also be provided separately or in any subcombination.

[0031] Throughout this specification, various aspects and components of the disclosure may be presented in a range format. The range format is included for convenience and should not be construed as limiting the scope of the disclosure. Thus, the description of a range should be considered as specifically disclosing all possible subranges and individual numerical values ​​within that range unless specifically indicated otherwise. For example, the description of a range such as 1 to 5 should be considered as specifically disclosing subranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 5, 3 to 5, etc., and individual and partial numbers within this range such as 1, 2, 3, 4, 5, 5.5, and 6, etc., unless an integer is required or implied by context. This is true regardless of the breadth of the disclosed range. If specific numerical values ​​are required, they will be set forth in the specification.

[0032] Throughout this specification the word "comprise" or variations such as "comprising" will be understood to mean the inclusion of a stated element, integer or step, or group of elements, integers or steps, but not the exclusion of any other element, integer or step, or group of elements, integers or steps.

[0033] Throughout this specification, the term "consisting essentially of" is intended to exclude elements that may materially affect the properties of the claimed composition.

[0034] As used herein, the terms "comprising", "comprise", and "comprises" are intended in all instances to be optionally interchangeable with the terms "consisting essentially of", "consist essentially of", "consist essentially of", "consisting of", "consist of" and "consists of", respectively.

[0035] As used herein, the term "about" encompasses any value or a tolerance of 10% of the value associated with that term.

[0036] As used herein, "curable" or "cured" refers to a material or composition that has been or can be cured (e.g., polymerized or crosslinked) by heating to induce polymerization and / or crosslinking; irradiating with light to induce polymerization and / or crosslinking; and / or mixing one or more components to induce polymerization and / or crosslinking. Mixing can be performed, for example, by combining two or more parts and mixing to form a homogenous composition. Alternatively, two or more parts can be provided as separate layers and allowed to intermix at an interface (e.g., spontaneously or by application of shear stress) to initiate polymerization.

[0037] "Substantially free" generally refers to the absence of that compound or component in the composition, except for trace amounts of impurities that may be present, which may be, for example, less than about 1%, less than 0.1%, less than 0.01%, less than 0.001%, or less than 0.0001% by weight of the total composition. The compositions described herein may also contain impurities in amounts, for example, less than about 2%, less than 1%, less than 0.5%, less than 0.1%, less than 0.01%, or less than 0.001%, or less than 0.0001% by weight of the total composition.

[0038] Here, "weight %" may be abbreviated as "wt%".

[0039] Conductive polymer composition The present disclosure is directed to providing improvements in conductive coatings, including improved stability, particularly at elevated temperatures. The present disclosure is directed to various research and development efforts directed to identifying agents that are compatible with coating compositions containing polyaniline conductive polymers and also provide the coatings with excellent thermal stability. The present disclosure also addressed the development of easily processable compositions for preparing effective coatings on various substrates, such as solution processable antistatic coatings for use on electronic circuit boards.

[0040] The thermal stabilizer, at least according to some examples described herein, may also provide effective compatibility for use with solution processable coating compositions that include polyaniline conductive polymers. The thermal stabilizer, at least according to some examples described herein, may also inhibit processes that cause degradation of the polyaniline conductive polymer present in the coating, especially when the coating is present in a high temperature environment.

[0041] It has also been found, in accordance with at least some examples described herein, that the addition of one or more thermal stabilizers to a coating or composition comprising one or more polyaniline conductive polymers can be used to: (a) limiting or reducing the deleterious degradation and / or loss of dopants; and / or (b) limiting the oxidation of polymer chains in conductive polymers;

[0042] For example, with respect to polyaniline sulfonates (e.g., PANI-DNNSA), it has been found that the introduction of one or more thermal stabilizers as described herein can inhibit, limit, or reduce: (i) desulfonation of a sulfonate salt (e.g., a DNNSA dopant); and / or (ii) Oxidation of the PANI polymer chains.

[0043] For example, with respect to polyaniline sulfonates (e.g., PANI-DNNSA), it has been found that the introduction of one or more first thermal stabilizers selected from alkali metal salts and, optionally, amphoteric metal oxides, and one or more second thermal stabilizers selected from the antioxidants described herein, can inhibit, limit, or reduce: (i) desulfonation of a sulfonate salt (e.g., a DNNSA dopant); and / or (ii) Oxidation of the PANI polymer chains.

[0044] It has also been found that one or more thermal stabilizers according to at least some of the embodiments described herein can be used in coatings comprising one or more solution processable polyaniline conductive polymers and, optionally, one or more film formers (e.g., PANI-DNNSA in a silicone dispersion) to form easily processable coatings having excellent thermal stability and desirable mechanical properties.

[0045] According to at least some aspects or embodiments of the thermal stabilizer and compositions and coatings thereof described herein, thermal stability can be provided such that at a temperature of about 150° C., the electrical resistance of the composition or coating comprising one or more conductive polymers (e.g., PANI sulfonates) remains less than about 100 MΩ for at least one week. Thermal stability can be provided in an air, vacuum, or inert atmosphere (such as nitrogen) environment. The compositions and coatings, according to at least some aspects or embodiments thereof described herein, can be stable at or below about 150° C.

[0046] In one aspect, embodiment, or example, there is provided a composition comprising a solution processable polyaniline conductive polymer in an organic solvent and one or more thermal stabilizers selected from an alkali metal salt, an amphoteric metal oxide, an antioxidant, or any combination thereof.

[0047] In another aspect, embodiment, or example, there is provided a composition comprising a solution processable polyaniline conductive polymer in an organic solvent, one or more thermal stabilizers selected from alkali metal salts, amphoteric metal oxides, antioxidants, or any combination thereof, optionally a film former, and optionally one or more additives.

[0048] The composition is a liquid composition (e.g., a liquid formulation) or a dry film coating. In one example, the composition is a liquid composition.

[0049] In another aspect, embodiment, or example, there is provided a liquid formulation comprising a solution processable polyaniline conductive polymer in an organic solvent, one or more first heat stabilizers selected from alkali metal salts and optionally amphoteric metal oxides, and one or more second heat stabilizers selected from antioxidants, wherein the total amount (wt % of the total formulation) of the one or more first heat stabilizers is about 2 wt % to 7 wt %, and the total amount (wt % of the total formulation) of the first and second heat stabilizers is less than about 9 wt %, wherein the first and second heat stabilizers are present in an organic solvent, and wherein the polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent.

[0050] The liquid formulation may further comprise one or more film-forming agents.

[0051] In another aspect, embodiment, or example, there is provided a liquid formulation comprising a solution processable polyaniline conductive polymer in an organic solvent, one or more first thermal stabilizers selected from alkali metal salts and optionally amphoteric metal oxides, one or more second thermal stabilizers selected from antioxidants, and one or more film-forming agents, wherein the total amount (wt% of the total formulation) of the one or more first thermal stabilizers is about 2wt% to 7wt%, and the total amount (wt% of the total formulation) of the first and second thermal stabilizers is less than about 9wt%, the first and second thermal stabilizers are present in an organic solvent, and the polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent. Even after the addition of the thermal stabilizers, the polyaniline salt remains dissolved in the organic solvent.

[0052] Conductive Compositions and Coatings Conductive coatings traditionally rely on solid conductive fillers such as silver or carbon black, which require solid infiltration, or incorporation by the filler of a sufficient volume of the coating so that the conductive particles can touch and electrons can flow throughout the coating. If infiltration is not achieved, the resin (often an insulator or dielectric) occupies the space between the conductive particles and electrons cannot flow throughout the coating. For spherical particles, the volume of the coating must be >28%. Conductive polymers in solid form must also meet the criteria to make a conductive coating. When a soluble conductive polymer is dispersed in a coating resin system in which it is soluble, the resulting solution (as opposed to a discreet ball of coiled polymer) can have a much smaller volume of conductive material that reaches infiltration with an extremely high aspect ratio.

[0053] It is known from the prior art that aniline monomers can be polymerized to polyaniline (PANI) before the addition of various additives, and then dissolved in a water / alcohol solvent system to create a conductive salt. It will be appreciated that it is very difficult to achieve a uniform particle size during dissolution of PANI. A significant portion of the PANI forms aggregates (i.e. the polymer rolls up into discreet balls), resulting in a decrease in electrical conductivity. The resulting PANI-DNNSA solution will therefore have a mixture of PANI-DNNSA and undissolved PANI aggregates. The inclusion of additives in such a solution will result in even larger aggregates and / or non-uniform dispersion. This type of process is industrially unreliable, especially during the formation of conductive films / coatings. Moreover, it is also difficult to predict the amount of additives required without significant trial and error.

[0054] The present inventors have advantageously discovered that PANI-DNNSA formed in-situ by polymerizing aniline and dopants in an organic solvent provides a highly conductive PANI-DNNSA solution. It has been unexpectedly discovered that the higher conductivity is a result of uniform distribution and better dissolution of the polymer salt in the organic solvent. In some embodiments or examples, the polyaniline conductive polymer solution has more than 95% of the polyaniline salt dissolved in the organic solvent. In other words, more than 95 wt% of the PANI-DNNSA is dissolved in the organic solvent and is not present as particles or aggregates or rolled up into discreet balls of polymer.

[0055] It will be appreciated that at least one of the drawbacks of preformed PANI-DNNSA salts, i.e., salts that are first formed and then dissolved in an organic solvent system, is that excess salt (e.g., DNNSA) may react with the polymer backbone, resulting in thermal instability. The inventors have surprisingly found compositions and processes for preparing thermally stable PANI-DNNSA solutions without the need to first isolate the polymer (e.g., PANI) or the polymer salt (e.g., PANI-DNNSA), where the polyaniline conductive polymer solution has more than 95% of the polyaniline salt dissolved in the organic solvent.

[0056] Heat stabilizer The thermal stabilizer may be selected from an alkali metal salt, an amphoteric metal oxide, an antioxidant, or any combination thereof. By introducing one or more first thermal stabilizers selected from an alkali metal salt and optionally an amphoteric metal oxide, and one or more second thermal stabilizers selected from the antioxidants described herein, the inventors can inhibit, limit, or reduce the desulfonation of sulfonates (e.g., DNNSA dopants); and / or the oxidation of PANI polymer chains, and can inhibit, limit, or reduce the precipitation of polyaniline conductive polymer from the organic solvent in which it is dissolved. One or more advantages of the present disclosure according to at least some embodiments or examples described herein is that the polyaniline conductive polymer dissolves in an organic solvent and remains dissolved in the organic solvent even after adding one or more thermal stabilizers, optional film-forming agents, and optional dispersants and / or additives.

[0057] In one example, the composition includes a thermal stabilizer selected from at least one antioxidant, at least one alkali metal salt, and at least one amphoteric metal oxide. In another example, the composition includes at least one alkali metal salt and at least one antioxidant. In another example, the composition includes at least one alkali metal salt.

[0058] In one example, the one or more heat stabilizers are present in the composition in an amount (wt% of the total composition) ranging from about 0.1 to about 9 wt%; about 0.5 to about 7 wt%; or about 1 to about 6 wt%. In another example, the total amount of heat stabilizer (wt% of the total composition) is provided in a range from about 0.5 to about 7 wt%; about 1 to about 7 wt%; or about 2 to about 7 wt%. For the listed amounts of heat stabilizer, the conductive polymer composition is optionally in the form of a liquid formulation or in the form of a dry film coating.

[0059] In one example, the formulation includes one or more first stabilizers. In another example, the formulation includes one or more first stabilizers and one or more second stabilizers. For example, the formulation includes one or more first heat stabilizers selected from alkali metal salts and, optionally, amphoteric metal oxides, and one or more second heat stabilizers selected from antioxidants.

[0060] In one example, the total amount (wt % of the total formulation) of the one or more first heat stabilizers is about 2 wt % to about 7 wt %. For example, the total amount (wt % of the total formulation) of the one or more first heat stabilizers is about 5 wt %.

[0061] In one example, the total amount (wt % of the total formulation) of the one or more secondary heat stabilizers is between about 0.5 wt % and about 3 wt %. In one example, the total amount (wt % of the total formulation) of the one or more secondary heat stabilizers is about 1 wt %.

[0062] In one example, the amount of amphoteric metal oxide (wt % of the total formulation), if present in the formulation, is less than about 3 wt %.

[0063] In other examples, one or more of the heat stabilizers (or all of the heat stabilizers) are present in an amount of at least about 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, or 9 wt%; or 0.2 wt%, and in any range of amounts (wt % of the total formulation) provided by a combination of any two upper and / or lower amounts thereof. In one example, the total amount (wt % of the total formulation) of the first heat stabilizer and the second heat stabilizer is about 9 wt %.

[0064] In another example, the composition is a liquid formulation including one or more conductive polymers and one or more thermal stabilizers, according to any aspect or embodiment thereof described herein. In another example, the one or more thermal stabilizers are added to the liquid formulation as a suspension or a solid. In another example, one or more of the first thermal stabilizer and the second thermal stabilizer present in the liquid formulation are provided to the liquid formulation as a suspension or a solid.

[0065] Alkali metal salts In one example, at least one alkali metal salt is present in the compositions described herein.

[0066] In one example, the alkali metal salt includes a cation of lithium (Li), sodium (Na), or potassium (K), beryllium (Be), magnesium (Mg), and / or calcium (Ca).

[0067] In one example, the counter ion of the metal cation in at least one alkali metal salt comprises hydroxide, carbonate, stearate, borosilicate, bicarbonate, metasilicate, phosphate, and / or hydrogen phosphate. In another example, the counter ion of the metal cation in the alkali metal salt comprises carbonate, bicarbonate, phosphate, and / or hydrogen phosphate. In yet another example, the counter ion of the metal cation in the alkali metal salt comprises carbonate. Examples of alkali metal salts include, but are not limited to, calcium carbonate (e.g., Omyacarb® 1 μm) (which may be surface treated (e.g., Omyacarb® 1T 1 μm)); calcium borosilicate (e.g., Halox®); calcium stearate; and / or calcium silicate Ca2SiO4 or wollastonite.

[0068] In one example, the alkali metal salt has an average particle size ranging from about 0.5 μm to about 5 μm; from about 0.5 μm to about 4 μm; from about 0.5 μm to about 3 μm; from about 0.5 μm to about 2 μm; or from about 0.5 μm to about 1 μm. In another example, the alkali metal salt has an average particle size of less than about 5 μm, 4 μm, 3 μm, 2 μm, 1 μm, or 0.5 μm. For example, the alkali metal salt has an average particle size of less than about 2 μm. In a preferred example, the alkali metal salt has an average particle size of less than about 1 μm.

[0069] For example, at least one alkali metal salt that is calcium carbonate is present in a composition that is a liquid formulation described herein, and the calcium carbonate has an average particle size of 1 μm.

[0070] Amphoteric Metal Oxides In one example, at least one amphoteric metal oxide is present in the conductive polymer composition described herein.

[0071] In another example, the conductive polymer composition includes at least one amphoteric metal oxide that is an oxide of zinc, cerium, zirconium, titanium, magnesium, yttrium, aluminum, and / or silicon. Examples include, but are not limited to, zirconia (ZrO2), titanium oxide (ZrO2), magnesium oxide (MgO), yttrium oxide (YO3), aluminum oxide (Al2O3), carbosil fumed silica, silicon oxide (e.g., TS-720), zinc oxide, and / or cerium oxide. In another example, the composition includes zinc oxide (ZnO) and / or cerium oxide (CeO2). In yet another example, the composition includes zinc oxide.

[0072] In another example, the amphoteric metal oxide has an average particle size that is less than about 5 μm, 4 μm, 3 μm, 2 μm, 1 μm, 950 nm, 900 nm, 850 nm, 800 nm, 750 nm, 700 nm, 650 nm, 600 nm, 550 nm, 500 nm, 450 nm, 400 nm, 350 nm, 300 nm, 250 nm, 200 nm, 150 nm, 100 nm, 50 nm, 40 nm, 30 nm, 20 nm, or 10 nm. Alternatively, the amphoteric metal oxide has an average particle size in the range of about 10 nm to about 100 nm; about 20 nm to about 90 nm; about 30 to about 80 nm; or about 60 to about 70 nm. For example, the amphoteric metal oxide has an average particle size in the range of about 30 nm to about 50 nm.

[0073] In one example, one or more of the amphoteric metal oxides are surface treated, for example, with a surface treatment that includes a polymeric dispersant. It will be appreciated that an advantage of one or more of the present disclosure according to at least some embodiments or examples described herein is that the surface treatment can render the surface of the metal oxide hydrophobic, aiding in dispersion.

[0074] Antioxidants In one example, at least one antioxidant is present in the conductive polymer composition described herein. In another example, at least two antioxidants (e.g., a primary antioxidant and a secondary antioxidant) are present in the conductive polymer composition described herein. One or more primary antioxidants may be added to act as radical scavengers to remove radicals such as peroxy radicals. The primary antioxidant may be sacrificial and, when partially or completely consumed, one or more polymers present in the conductive polymer composition may begin to degrade. One or more secondary antioxidants may be added to remove harmful species such as organic peroxides that may be formed by the action of the primary antioxidant.

[0075] Examples of antioxidants include, but are not limited to, substituted (hindered) phenols which may contain a propionate group, phosphites P(OR)3 (where each R is independently an aryl or phenyl group), thioethers, thiols, disulfides, and organosulfurs including combinations thereof.

[0076] In one example, the conductive polymer composition includes at least one hindered phenol antioxidant that includes at least one 3,5-di-tert-butyl-4-hydroxyphenyl group.

[0077] In another example, the conductive polymer composition includes one or more compounds selected from pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (e.g., Irganox 1010), n-octadecyl(3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate) (e.g., Irganox 1076), ethylene bis(oxyethylene) bis-(3-(5-tert-butyl-4-hydroxy-m-tolyl)-propionate) (e.g., Irganox 245), and combinations thereof.

[0078] In yet another example, the composition comprises one or more compounds selected from bis(2,4-dicumylphenyl)pentaerythritol diphosphate (e.g., Doverphos 9228), distearyl pentaerythritol diphosphite (e.g., Doverphos S-682), didodecyl 3,3′-thiodipropionate, tris(2,4-ditert-butylphenyl)phosphite (e.g., Irganox 168), and combinations thereof.

[0079] solvent The conductive polymer compositions disclosed herein are present in one or more solvents. The one or more solvents may be selected to provide a fluid carrier for the one or more conductive polymers in the compositions described herein.

[0080] It will be understood that the conductive polymers described herein provide solution-processable conductive polymers. A "solution-processable" conductive polymer refers to a conductive polymer that is soluble in one or more solvents, for example, at least about 95 wt% of the conductive polymer is soluble in one or more solvents. For example, a polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in one or more solvents (e.g., an organic solvent such as toluene). The solvent can be provided by one or more organic solvents described herein. In another example, the organic solvent is an aromatic organic solvent. In another example, the organic solvent is a non-aqueous organic solvent.

[0081] The organic solvent may be selected from the group including aromatics, halogenated aromatics (e.g., chlorinated aromatics), halogenated aliphatic hydrocarbons (e.g., chlorinated aliphatic hydrocarbons), aliphatic hydrocarbons, glycols, ethers, glycol ethers, esters, alcohols, ketones, and combinations thereof. It will be appreciated that the alcohol may be a water-immiscible alcohol having at least a medium alkyl chain or aryl group. The water-immiscible alcohol may be n-butanol or a larger alkyl chain alcohol. It will be appreciated that the ketone may be a water-immiscible ketone having at least a medium chain ketone, such as methyl ethyl ketone or a ketone having a larger alkyl chain.

[0082] The organic solvent may be selected from the group including aromatics, halogenated aromatics, halogenated aliphatic hydrocarbons, aliphatic hydrocarbons, glycols, ethers, glycol ethers, esters, alcohols, ketones, and combinations thereof. In another example, the organic solvent is selected from aliphatic or aromatic hydrocarbons (e.g., toluene and / or naphtha).

[0083] In another example, the organic solvent is a non-aqueous organic solvent selected from toluene, xylene, mesitylene, cymene, terpenes, and combinations thereof. In another example, the organic solvent is a non-aqueous organic solvent selected from aromatic hydrocarbons, such as toluene and xylene. In another example, the organic solvent is a cyclic amide, such as n-methyl-2-pyrrolidone.

[0084] The organic solvent can also be selected to dissolve the acid dopant (i.e., the protonic acid), for example, the protonic acid of the DNNSA can be provided in an organic solvent such as a glycol ether (e.g., 2-butoxyethanol), a hydrocarbon (e.g., heptane), or an aromatic hydrocarbon (e.g., toluene and / or xylene). In one example, the acid dopant is dissolved in toluene.

[0085] Suitable exemplary liquid solvents include aromatics such as xylene, toluene or alkylnaphthalene; chlorinated aromatic or chlorinated aliphatic hydrocarbons such as chlorobenzene, chloroethylene or methylene chloride; aliphatic hydrocarbons such as cyclohexane or paraffins (e.g. mineral oil fractions); alcohols such as butanol, isobutanol or glycols, and their ethers and esters, for example 2-butoxyethanol; ketones such as methyl ethyl ketone, methyl isobutyl ketone or cyclohexanone. For example, the organic solvent is toluene. It will be understood that polyaniline or polyaniline salts are dissolved in the organic solvent, i.e. toluene. For example, a polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent.

[0086] In some examples, the organic solvent may contain less than about 800 ppm water, such as less than about 700 ppm, less than about 600 ppm, less than about 500 ppm, less than about 400 ppm, less than about 300 ppm, less than about 200 ppm, or less than about 100 ppm water. Anhydrous solvents may also be used. For example, the organic solvent is substantially free of water.

[0087] The solvent may contain incidental impurities, for example in amounts (wt % of the total formulation) of less than about 2, 1, 0.5, 0.1, 0.05, 0.01, 0.005, or 0.001 wt %.

[0088] The solvent may be present in an amount less than about 99 wt%, 98 wt%, 95 wt%, 90 wt%, 85 wt%, 80 wt%, 75 wt%, 70 wt%, 65 wt%, 60 wt%, 55 wt%, 50 wt%, 45 wt%, or 40 wt% (based on the total weight of the formulation or its components). In one example, the composition includes one or more organic solvents, where the amount of organic solvent is present in an amount (wt% of the total formulation) ranging from about 35 to about 99 wt%, from about 50 to about 90 wt%, or from about 35 to about 60 wt%. In another example, the amount of organic solvent is present in an amount (wt% of total formulation) of at least about 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%; or 95 wt%. The solvent can be within a range defined by any two of these upper and / or lower limits.

[0089] Conductive Polymers The compositions described herein include one or more conductive polymers. It is understood that the conductive polymer can provide a solution-processable conductive polymer. A "solution-processable" conductive polymer refers to a conductive polymer that is soluble in one or more solvents. For example, a conductive polymer salt can be provided, where at least about 0.1.0.5, 1, 5, 10, 25, 30, 35, 40, 45, or 50 grams of the conductive polymer salt is soluble in 100 mL of organic solvent when measured at standard room temperature and pressure.

[0090] It will be understood that a conductive polymer is a polymer having a conjugated chain structure. Unless otherwise defined, a conductive polymer refers to any organic polymer or copolymer capable of conducting electricity, and it will be understood that it may include, for example, polymers that are semiconductors. A conductive polymer may require further processing to provide the desired conductance properties. An example of a conductive polymer is a polyaniline salt.

[0091] It will be understood that conductive polyaniline includes polymeric polyaniline that has been doped with a protonic acid and is in the form of a polyaniline salt.

[0092] The polyaniline conductive polymer can be, for example, polyaniline emeraldine salt. In one example, the solution-processable conductive polymer salt is a solution-processable conductive polymer sulfonate. The salt can be dinonylnaphthalene sulfonate (DNNSA), methanesulfonate (MSA), camphorsulfonate (CSA), p-toluenesulfonate (TSA), dodecylbenzenesulfonate (DBSA), dinonylnaphthalenesulfonate (DNNSA), polystyrenesulfonate, or a combination thereof. In one example, the conductive polymer salt is dinonylnaphthalenesulfonate (DNNSA). In another example, the conductive polymer salt is an organic solvent soluble conductive polymer salt. An organic solvent soluble conductive polymer salt can be provided, where at least about 0.1.0.5, 1, 5, 10, 25, 30, 35, 40, 45, or 50 grams of the conductive polymer salt is soluble in 100 mL of organic solvent (e.g., toluene) when measured at standard room temperature and pressure.

[0093] According to some aspects or embodiments described herein, the conductive polymer is a solution processable polyaniline emeraldine salt. The solution processable polyaniline salt can be a solution processable polyaniline sulfonate. In some aspects or embodiments, the polyaniline salt can be a sulfonate, and the sulfonic acid can be methanesulfonic acid (MSA), camphorsulfonic acid (CSA), p-toluenesulfonic acid (TSA), dodecylbenzenesulfonic acid (DBSA), dinonylnaphthalenesulfonic acid (DNNSA), or a combination thereof. The conductive polymer can be polyaniline methanesulfonate (PANI-MSA). The conductive polymer can be polyaniline camphorsulfonate (PANI-CSA). The conductive polymer can be polyaniline-p-toluenesulfonate (PANI-TSA). The conductive polymer can be polyaniline dodecylbenzenesulfonate (PANI-DBSA). The conductive polymer can be polyaniline dinonyl naphthalene sulfonate (PANI-DNNSA).

[0094] Polyaniline can exist in three oxidation states: leucoemeraldine (white), emeraldine (green) and pernigraniline (blue / purple). The repeat unit of formula 1 below provides x as half the degree of polymerization. TIFF2024508584000001.tif30170

[0095] Leucoemeraldine is the fully reduced state (e.g. n=1, m=0). Pernigraniline is the fully oxidized state, with imine linkages instead of amine linkages (n=0, m=1). Polyaniline can be in one of these three states or a mixture of them. The emeraldine form of polyaniline (n=m=0.5) is called emeraldine base (EB) when neutral, but when protonated is called emeraldine salt (ES) with the imine nitrogen protonated by acid. Protonation promotes delocalization of the otherwise trapped diiminoquinone-diaminobenzene state.

[0096] In one example, the conductive polymer is a conductive polymer salt, such as a sulfonate or phosphonate. In one example, the conductive polymer is a polyaniline sulfonate. Examples of salts include salts of methanesulfonic acid, salts of camphorsulfonic acid, salts of p-toluenesulfonic acid, salts of dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonate, and combinations thereof.

[0097] In another example, the composition comprises a polyaniline sulfonate selected from polyaniline methanesulfonic acid, polyaniline camphorsulfonic acid, polyaniline p-toluenesulfonic acid, polyaniline dodecylbenzenesulfonic acid, polyaniline dinonylnaphthalenesulfonate, and combinations thereof.

[0098] In yet another example, the conductive polymer is a polyaniline sulfonate which is polyaniline dinonyl naphthalene sulfonate.

[0099] Polyaniline conductive polymers are organic solvent soluble polyaniline salts prepared in situ by polymerizing aniline monomers with protonic acids in an organic solvent.

[0100] It will be understood that the compositions described herein include polyaniline salts. Polymers (e.g., polyaniline (PANI)) are generally not conductive until they are converted to a salt form (e.g., PANI-DNNSA).

[0101] In some aspects or embodiments, each individual polymer chain of the polyaniline or any salt thereof may be independently composed of between about 100 and 1500 individual monomer units. The number of individual monomer units may be at least about: 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, or 1200. The number of individual monomer units may be less than about: 1500, 1400, 1300, 1200, 1100, 1000, 900, 800, 700, 600, or 500. The number of individual monomer units may be between about: 300 to 1400, 500 to 1300, 600 to 1200, or 700 to 1100. The number of individual monomer units in an individual polymer chain may be within a range defined by any lower and / or upper limits, as discussed above.

[0102] The polyaniline or polyaniline salt may have a number average molecular weight of at least 10,000. For example, the number average molecular weight may be at least about 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, or 80,000. The number average molecular weight may be in the range of about 1,000 to 120,000, 20,000 to 115,000, 30,000 to 110,000, 40,000 to 105,000, 50,000 to 100,000, or 60,000 to 100,000. The number average molecular weight may be less than about 120,000, 110,000, 100,000, 90,000, 80,000, 70,000, 60,000, 50,000, or 40,000. The number average molecular weight can be in a range defined by any lower and / or upper limits, as discussed above.

[0103] According to at least some aspects or embodiments where the conductive polymer is a conductive polymer sulfonate (e.g., PANI sulfonate), the sulfur to nitrogen ratio (S / N ratio) of the conductive polymer component of the coating may be within the range of about: 0.1 to 0.5, 0.15 to 0.45, or 0.2 to 0.4. The S / N ratio may be less than about: 0.5, 0.45, 0.4, 0.35, 0.3, or 0.25. The S / N ratio may be at least about: 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or 0.5. The S / N ratio may be within the range defined by any lower and / or upper limits, as discussed above. For example, the S / N ratio of polyaniline sulfonate may be within the range of about: 0.1 to 0.5, 0.15 to 0.45, or 0.2 to 0.4. The signal to noise ratio of the polyaniline sulfonate may be less than about: 0.5, 0.45, 0.4, 0.35, 0.3, or 0.25. The signal to noise ratio of the polyaniline sulfonate may be at least about: 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or 0.5. The signal to noise ratio of the polyaniline sulfonate may be in a range defined by any lower and / or upper limits as described above. It will be understood that these ratios refer to precipitated solid conductive polymers and not to cast thin films of conductive polymers.

[0104] It will be understood that the conductive polymer of the present disclosure can be provided with high purity and dissolved in an organic solvent. In some aspects or embodiments, the purity of the conductive polymer can be within the range of about (by wt%): about 70 to about 99 wt%, about 75 to about 98 wt%, about 80 to about 97 wt%, about 85 to about 96 wt%, or about 90 to 95 wt%. The purity of the conductive polymer can be at least about (by wt%): 70, 75, 80, 85, 90, 95, or 99 wt%. The purity of the conductive polymer can be less than about (by wt%): 99, 98, 97, 96, 95, 90, 85, 80, or 75 wt%. The purity of the conductive polymer can be within a range defined by any lower and / or upper limits as described above. It will be understood that the conductive polymer can be dissolved or dispersed in an organic solvent for coating on a substrate. In other words, the conductive polymer, according to at least some aspects or embodiments, is present in a solid phase and can be dissolved or dispersed in an organic solvent so that the conductive polymer can be applied or coated onto a scaffold or substrate.

[0105] In one example, the compositions described herein (optionally in the form of a liquid formulation or a dry film composition) comprise a conductive polymer in an amount (wt% of the total composition) in the range of about 1 to about 75 wt%; about 5 to about 70 wt%; about 10 to about 65 wt%; about 15 to about 50 wt%; about 10 to about 40 wt%; about 40 wt% to about 80 wt%; about 74 to about 85 wt%; or about 45 to about 55 wt%. In another example, the conductive polymer compositions described herein (optionally in the form of a liquid formulation or a dry film composition) comprise a conductive polymer in an amount (by weight % of the total composition) of at least about: 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%; or less than about: 80 wt%, 75 wt%, 70 wt%, 65 wt%, 60 wt%, 55 wt%, 50 wt%, 45 wt%, 40 wt%, 35 wt%, 30 wt%, 25 wt%, 20 wt%, 15 wt%, 10 wt%, or 5 wt%. The conductive polymer can be within the range provided by any two of these upper and / or lower limits.

[0106] In one example, the liquid formulation or dry film composition includes the conductive polymer in an amount between about 80 wt% and about 90 wt% (wt% of the total formulation). For example, the liquid formulation or dry film composition includes the conductive polymer in an amount between about 80 wt% and about 85 wt% (wt% of the total formulation).

[0107] It will be appreciated that the polyaniline conductive polymer is an organic solvent soluble polyaniline conductive polymer salt made in-situ by polymerizing aniline monomer with a protonic acid in an organic solvent (e.g., toluene) and remains dissolved in the organic solvent. In other words, the polyaniline conductive polymer, at least according to some aspects or embodiments, is in a liquid phase and is dissolved in an organic solvent so that the polyaniline conductive polymer can be applied or coated onto a scaffold or substrate. Advantageously, the polyaniline conductive polymer or polyaniline conductive polymer salt (e.g., PANI-DNNSA) formed in-situ in an organic solvent provides a highly conductive polymer or polymer salt solution, thus avoiding and / or preventing the formation of undesirable undissolved polymer aggregates. For example, the polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent. In other words, at least 95 wt% of the PANI-DNNSA is dissolved in the organic solvent and is not present as particles or aggregates or rolled up into discreet balls of polymer.

[0108] In one example, the liquid formulation or dry film composition includes the conductive polymer in an amount between about 30 wt% and about 40 wt% (wt% in organic solvent). For example, the liquid formulation or dry film composition includes the conductive polymer in an amount of about 35 wt% (wt% in organic solvent).

[0109] Film-forming agents The compositions described herein may further comprise one or more film-forming agents. For example, the conductive polymer composition may comprise or consist of a film-forming agent and optionally one or more dispersing agents. In one example, the composition according to any aspect or embodiment described herein is a curable coating composition that comprises or consists of one or more conductive polymers, one or more heat stabilizers, a film-forming agent, one or more solvents, and optionally one or more dispersing agents.

[0110] It will be appreciated that the film former can provide a polymer matrix or dispersion in which the conductive polymer and thermal stabilizer are incorporated. The film former (e.g., silicone) can provide additional properties to the coating, such as various mechanical, thermal, and stability properties.

[0111] In one example, the film former includes a polymer, optionally an initiator, optionally a chain extender, and optionally a polymerizable monomer, comonomer, or copolymer. The film former can be a silicone or polysiloxane.

[0112] The film former may include any polymer (e.g., copolymer) or polymerizable component, such as a reactive monomer (e.g., resin) that can form a polymer in the coating. The polymer component may consist of a polymer, a copolymer, a resin, a monomer, and a comonomer. Some examples of the polymer component include one or more of polysiloxane, polyolefin, polyurethane, polyacrylic acid, polyacrylate, polyether, polyester, polyketide, polyurethane, polyamide, polysilazane, or any copolymer thereof. In one example, the film former includes a polymer selected from a siloxane (e.g., silicone), or a component that forms a siloxane. The siloxane may be a polysiloxane.

[0113] Examples of siloxanes or polysiloxanes may be those substituted with hydrogen or alkyl groups. Other examples include silanamine, 1,1,1-trimethyl N-(trimethylsilyl)-, hydrolysis products with silica, polydimethylsiloxane, methyltrimethoxysilane, octamethylcyclotetrasiloxane, dimethyldimethoxysilane.

[0114] In another embodiment, the film forming agent is Nusil TM(R-1009) RTV silicone dispersion coating. The silicone dispersion coating may be a high strength, flowable one part RTV silicone rubber dispersed in VM&P Naphtha. The silicone dispersion coating may include an oxime cure system based on 2-butanone, O,O',O''-(methylsilylidyne)trioxime and dibutyltin dilaurate catalyst. Another example includes Nusil as a two part silicone elastomer dispersed in xylene with a platinum cure system. TM (R-2180). Another example is Dowsil TM (3145) RTV MIL-A-46146, which can provide adhesive sealant properties.

[0115] It will be understood that "film former" can encompass any film former component, for example, any monomers, comonomers, resins, copolymers, polymers, chain extenders, and initiators used to provide the film former.

[0116] The film former (e.g., silicone) may be provided in the dry film composition or coating in an amount (wt % of the total composition or coating) of about 1 to 15, 5 to 15, 1 to 10, or 5 to 10. The film former may be provided in the dry film composition or coating in an amount (wt % of the total composition) of at least about 1, 2, 3, 4, 5, 10, 15; or less than about 15, 10, 5, 4, 3, 2, or 1. The film former may be within the range provided by any two of these upper and / or lower amount limits.

[0117] Dispersants The compositions described herein may optionally include one or more film-forming agents.

[0118] Dispersants may include primary alcohol-based nonionic surfactants (eg, Merpol 4481, DuPont) and alkylphenol-formaldehyde-disulfide condensates (eg, Clariants 1494).

[0119] In one example, the dispersant is Disperbyk TM Dispersants, e.g. Disperbyk It may be a wetting and dispersing additive, such as 2050. The dispersing agent may be provided as a solution of an acrylate copolymer having basic affinity groups.

[0120] In another example, the dispersant is Disperbyk TM 2155, which is a wetting and dispersing additive. The dispersant may be provided as a solution of a block copolymer having pigment-affining groups.

[0121] In another example, the dispersant is Tegomer TM (eg, M-Si 2650), which is a comb-structured organomodified siloxane containing non-reactive aromatic groups.

[0122] In another example, the dispersing agent may be a polyglycerin modified silicone, such as polyglyceryl-3-polydimethylsiloxyethyl dimethicone.

[0123] In another example, the dispersant may be a silicone acrylate such as acrylates / ethylhexyl acrylate / dimethicone methacrylate copolymer.

[0124] In another example, the dispersant may be a monocarbinol terminated polydimethylsiloxane.

[0125] The dispersing agent (e.g., organosiloxane) may be provided in the dry film composition or coating in an amount (wt % of the total composition or coating) of about 0.1 to 15, 2 to 15, or 5 to 15. The dispersing agent may be provided in the dry film composition or coating in an amount (wt % of the total solvent or composition) of at least about 0.1, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10; or less than about 15, 10, 9, 8, 7, 6, 5, 4, 3, or 2. The film former may be within the range provided by any two of these upper and / or lower amount limits.

[0126] Additives In one example, the conductive polymer composition, coating, or coating composition further comprises or further consists of one or more additional additives.

[0127] In one example, additives are present in an amount of less than about 10% based on the weight of the composition.For example, the combined amount of all additives, if present, can be provided in an amount of about: 2%, 1%, 0.1%, or 0.05%.The amount of all additives, if present, can be provided in an amount ranging between any two of the above values, for example, between about 0.01% and about 2%, between about 0.05% and about 1%, between about 0.1% and about 2%, or between about 0.5% and about 2% (based on the total weight of the composition).

[0128] Any reference to "substantially free" generally refers to the absence of that compound component in the composition, except for trace amounts of impurities that may be present, which may be, for example, less than about: 1 wt%, 0.1 wt%, 0.01 wt%, 0.001 wt%, 0.0001 wt%, by weight of the total composition. The compositions described herein may also contain impurities in amounts, for example, less than about: 2 wt%, 1 wt%, 0.5 wt%, 0.1 wt%, 0.01 wt%, or 0.001 wt%, or 0.0001 wt%, by weight of the total composition.

[0129] It will be understood that film formers, dispersants, or other additives, if present, are different chemical entities than the heat stabilizers described in this disclosure.

[0130] liquid formulation The composition is in the form of a liquid formulation. The liquid formulation may comprise one or more polyaniline conductive polymers and one or more thermal stabilizers in an organic solvent according to any aspect or embodiment described herein.

[0131] It will be appreciated that the conductive polymer may provide good solution processability, such as being soluble in one or more solvents as described herein.

[0132] In one example, the one or more solvents are organic solvents according to any aspect or embodiment described herein. For example, the organic solvent is selected from aromatic organic solvents. In another example, the organic solvent is toluene. In one example, the conductive polymer is an organic solvent-soluble conductive polymer salt made in-situ by polymerizing aniline monomers and protonic acid in an organic solvent (e.g., toluene).

[0133] The thermal stabilizer (the first thermal stabilizer and / or the second thermal stabilizer) can be added to the conductive polyaniline in an organic solvent to form a dispersion in the organic solvent.

[0134] The inventors have unexpectedly found that formulations described herein comprising a polyaniline conductive polymer (e.g., PANI-DNNSA) in an organic solvent (e.g., toluene) and one or more thermal stabilizers can significantly improve the conductivity of a coating compared to a formulation consisting of a polyaniline conductive polymer (e.g., PANI-DNNSA) alone in an organic solvent (e.g., toluene).

[0135] In one example, the liquid formulations described herein can be used to form conductive coatings (dry film coatings) that are at least 5 times more conductive than coatings formed using formulations of polyaniline conductive polymers in organic solvents. For example, the liquid formulations described herein can be used to form polyaniline conductive coatings (dry film coatings) that are at least 10 times more conductive than coatings formed using formulations of polyaniline conductive polymers in organic solvents.

[0136] In another example, the liquid formulation comprises (based on wt% of the total formulation): any one or more conductive polymers in a total amount of about 80 to 93 wt % in an organic solvent; any one or more of heat stabilizers in a total amount of about 2 to 7 wt %; Optionally, one or more film-forming agents in a total amount of about 1 to 10 wt %; and Optionally, one or more dispersing agents in a total amount of about 0.1 to 15 wt %.

[0137] In another example, a liquid formulation is provided that includes one or more of the following (wt% of total formulation): a conductive polyaniline salt in an organic solvent in an amount of about 80 to 90 wt %; one or more of the first heat stabilizers in a total amount of about 2 to 7 wt %; one or more second heat stabilizers in a total amount of about 0.5 to 3 wt %; Optionally, a silicone film former in a total amount of about 5 to 15 wt %; and Optionally, an organosiloxane dispersant in a total amount of about 0.1 to 25 wt %.

[0138] The conductive polymer may be provided in the liquid formulation in an amount (wt % of the total formulation or composition in organic solvent) of about 1 to 93, 5 to 85, 10 to 80, 15 to 60, or 20 to 50. The conductive polymer may be provided in the liquid formulation in an amount (wt % of the total formulation or composition) of at least about 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or 90; or less than about 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, or 5. The conductive polymer may be within the range provided by any two of these upper and / or lower amount limits. For example, the amount of polyaniline conductive polymer provided in the organic solvent (wt % of the total formulation) may be between about 80 wt % and about 90 wt %. In a preferred example, the amount of polyaniline conductive polymer provided in the organic solvent (wt % of the total formulation) may be between about 80 wt % and about 85 wt %.

[0139] The heat stabilizer may be provided in the liquid formulation in an amount (wt% of the total formulation or composition) of about 1 to 7, or 2 to 7. The heat stabilizer may be provided in the liquid formulation in an amount (wt% of the total formulation or composition) of at least about 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, or 9; or less than about 9, 8, 7, 6, 5, 4, 3, 2, 1, or 0.5. The heat stabilizer may be within the range provided by any two of these upper and / or lower amount limits.

[0140] In one example, the one or more first heat stabilizers may be provided in the liquid formulation in a total amount (wt %) between about 2 wt % and about 7 wt % of the total formulation. In one example, the one or more first heat stabilizers may be provided in the liquid formulation in a total amount (wt %) of about 5 wt % of the total formulation.

[0141] In one example, the one or more secondary heat stabilizers may be provided in the liquid formulation in an amount between about 0.5 wt% and about 3 wt% (wt % of the total formulation). In one example, the one or more secondary heat stabilizers may be provided in the liquid formulation in a total amount of about 1 wt% (wt % of the total formulation).

[0142] In one example, the first heat stabilizer and the second heat stabilizer may be provided in the liquid formulation in a combined amount (weight % of the total formulation) of less than about 9 wt %.

[0143] The film former may be provided in the liquid formulation in an amount of about 1 to 15, 1 to 14, or 1 to 10 (wt% of the total formulation or composition). The film former may be provided in the liquid formulation in an amount of at least about 2, 5, 10, or 15; or less than about 20, 15, or 10 (wt% of the total formulation or composition). The film former may be within the range provided by any two of these upper and / or lower amounts. For example, the film former (e.g., silicone) may be provided in the liquid formulation in an amount of about 5 wt% to about 15 wt% (wt% of the total formulation). In one example, the film former (e.g., silicone) may be provided in the liquid formulation in an amount of about 10 wt% (wt% of the total formulation).

[0144] The dispersants and / or additives, when present, will be in the amounts disclosed above.

[0145] Membranes and Coatings The compositions described herein may be provided in the form of a film, such as a dry film composition or a coating.

[0146] In one example, the dry film composition includes (based on wt % of the total composition): any one or more of the conductive polymers in a total amount of about 80 to 93 wt %; any one or more of heat stabilizers in a total amount of about 4 to 20 wt %; Optionally, one or more film-forming agents in a total amount of about 5 to 20 wt %; and Optionally, one or more dispersing agents in a total amount of about 0.1 to 15 wt %.

[0147] The conductive polymer may be provided in the dry film composition or coating in an amount (wt % of the total composition or coating) of about 1 to 90, 5 to 80, 10 to 70, 15 to 60, or 20 to 50. The conductive polymer may be provided in the dry film composition or coating in an amount (wt % of the total composition) of at least about 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or 90; or less than about 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, or 5. The conductive polymer may be within the range provided by any two of these upper and / or lower amount limits. For example, the amount of conductive polymer provided in the liquid formulation (wt % of the total formulation) may be between about 80 wt % and about 90 wt %. In a preferred example, the amount of conductive polymer provided in the liquid formulation (wt % of the total formulation) may be between about 80 wt % and about 85 wt %.

[0148] The heat stabilizer may be provided in the dry film composition or coating in an amount (wt % of the total composition or coating) of about 4 to about 20, or about 4 to about 20. The heat stabilizer may be provided in the dry film composition or coating in an amount (wt % of the total composition) of at least about 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20; or about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, or 4. The heat stabilizer may be within the range provided by any two of these upper and / or lower amount limits.

[0149] In one example, the one or more first heat stabilizers may be provided in the liquid formulation in a total amount (wt %) between about 4 wt % and about 15 wt %. In one example, the one or more first heat stabilizers may be provided in the liquid formulation in a total amount (wt %) of about 15 wt %.

[0150] In one example, the one or more secondary heat stabilizers may be provided in the liquid formulation in an amount between about 4 wt% and about 15 wt% (wt% of the total formulation). In one example, the one or more secondary heat stabilizers may be provided in the liquid formulation in a total amount less than about 15 wt% (wt% of the total formulation).

[0151] In one example, the first heat stabilizer and the second heat stabilizer may be provided in the liquid formulation in a combined amount (weight % of the total formulation) of less than about 20 wt%.

[0152] The film former (e.g., silicone) may be provided in the dry film composition in an amount of about 1 to 20, 5 to 20, or 10 to 20 (wt% of the total composition or coating). The film former may be provided in the dry film composition or coating in an amount of at least about 5, 10, 15, 20; or less than about 20, 15, or 10 (wt% of the total composition). The film former may be within the range provided by any two of these upper and / or lower amount limits. The film former may be within the range provided by any two of these upper and / or lower amount limits. For example, the film former (e.g., silicone) may be provided in the liquid formulation in an amount of about 10 wt% to about 20 wt% (wt% of the total formulation). In one example, the film former (e.g., silicone) may be provided in the liquid formulation in an amount of about 20 wt% (wt% of the total formulation).

[0153] The dispersants and / or additives, when present, will be in the amounts disclosed above.

[0154] The dry film composition or coating may contain relatively small amounts of residual solvent or impurities, for example, solvent in amounts less than about: 1, 0.5, or 0.1 wt % (wt % of total composition or coating).

[0155] The coating compositions described herein may be provided as commercial and industrial coating formulations. The coating formulation does not require dissolving the polyaniline conductive polymer salt in a solvent, since the polyaniline salt is already prepared in an organic solvent and used in the prepared organic solvent (e.g., toluene). Such liquid formulations can be prepared without further dissolution or additional solvents by adding heat stabilizers, film formers, optional dispersants and / or additives to the organic solvent in which the polyaniline conductive polymer salt is dissolved. The main advantage of the liquid formulations described herein is that they can be used as coating formulations without further dissolution or manipulation.

[0156] In one example, the liquid formulations described herein can be used to form conductive coatings (dry film coatings) that are at least 5 times more conductive than coatings formed using formulations of conductive polymers in organic solvents. For example, the liquid formulations described herein can be used to form conductive coatings (dry film coatings) that are at least 10 times more conductive than coatings formed using formulations of conductive polymers in organic solvents.

[0157] Coatings Disclosed herein are coating layers provided by the compositions described herein, which can form part of a coating system.

[0158] Also disclosed herein are substrates comprising one or more coating layers, at least one of the coating layers comprising a composition described herein.

[0159] Also disclosed herein is a coating applied to an optionally coated substrate, the coating comprising any of the compositions described herein or coatings thereof.

[0160] Also disclosed herein is a coating system comprising: (i) a substrate which may be coated; (ii) one or more optional postcoat layers; and (iii) one or more layers located between i) and (ii) comprising a composition described herein.

[0161] The coating may comprise or consist of the coating composition according to any aspect or embodiment as described herein.

[0162] As an example, the coatings or coating layers described herein are antistatic coatings.

[0163] In another example, the coatings or coating layers described herein include a polymer, such as a polysiloxane.

[0164] In another example, the coatings or coating layers described herein have a thickness in the range of about 1 to about 10 μm, or at least about: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm.

[0165] Suitable substrates include metals and metal alloys (eg, steel or aluminum), as well as composites such as epoxy fiberglass sheets, carbon fiber reinforced composites, Teflon, or glass.

[0166] For example, a coating may be applied to a substrate that may be coated, the coating comprising or consisting of a composition according to any aspect, embodiment, or example described herein.

[0167] In one example, the composition is in the form of a coating having a resistance of less than about 200 MΩ, about 150 MΩ, about 100 MΩ, about 50 MΩ, about 10 MΩ, or about 5 MΩ.

[0168] In one example, the resistance is substantially the same over a period of, for example, about 12 hours, about 24 hours, about 48 hours, about 72 hours, about 96 hours, or about one week.

[0169] In another example, the composition is in the form of a coating having: (a) a coating having a resistance of less than about 200 MΩ, about 150 MΩ, about 100 MΩ, about 50 MΩ, about 10 MΩ, or about 5 MΩ; (b) a temperature range or selected temperature; (c) for a certain period of time, Optionally: (i) the temperature range or selected temperature is within the range of: about 70° C. to about 300° C., about 70° C. to about 250° C., about 70° C. to about 200° C., about 70° C. to about 150° C., about 70° C. to about 100° C., about 70° C. to about 300° C., about 100° C. to about 300° C., about 150° C. to about 300° C., about 200° C. to about 300° C., about 250° C. to about 300° C.; or a temperature of at least about: 70° C., 90° C., 110° C., 130° C., 150° C., 170° C., 190° C., 210° C., 230° C., 250° C., 270° C., or 290° C.; (ii) the period of time is at least: about 12 hours, about 24 hours, about 48 hours, about 72 hours, about 96 hours, or about one week; and / or (iii) Any analyses are performed in air.

[0170] Methods for Preparing and Applying Coatings The coating compositions described herein can be provided in commercial and industrial coating formulations.

[0171] In another aspect, embodiment, or example, there is provided a method for preparing a liquid formulation comprising mixing (i) one or more first thermal stabilizers selected from alkali metal salts and optionally amphoteric metal oxides, (ii) one or more second thermal stabilizers selected from antioxidants, with (iii) a solution processable polyaniline conductive polymer dissolved in an organic solvent to form a liquid formulation, wherein the polyaniline conductive polymer is an organic solvent soluble polyaniline conductive polymer salt made in-situ by polymerizing aniline monomers with a protonic acid in an organic solvent, the total amount (wt% of the total formulation) of the one or more first thermal stabilizers is about 2 wt% to about 7 wt%, the total amount (wt% of the total formulation) of the first thermal stabilizer and the second thermal stabilizer is less than about 9 wt%, and the polyaniline conductive polymer solution has more than 95% polyaniline salt dissolved in the organic solvent. Even after the addition of the thermal stabilizers, the polyaniline salt remains dissolved in the organic solvent. In one example, the method further comprises (iv) mixing one or more film-forming agents into the liquid formulation. It will be understood that the method for preparing a liquid formulation described in any one or more aspects, embodiments, or examples can be used to form a conductive coating composition. In one example, the polyaniline conductive polymer dissolved in an organic solvent is passed through a filter with a pore size of less than about 1 μm before adding the thermal stabilizer. In another example, the polyaniline conductive polymer dissolved in an organic solvent is passed through a filter with a pore size between about 0.005 μm and about 1 μm before adding the thermal stabilizer.

[0172] The coating composition may be applied in a variety of physical forms.

[0173] In one example, a method for preparing a coating system includes: (i) applying a coating composition described herein to a substrate that may be coated; and (ii) optionally applying one or more postcoat layers to the coating present on the optionally coated substrate.

[0174] FIG. 3 provides another example of a method for preparing a coating comprising a conductive polymer thermally stabilized with one or more thermal stabilizers. An optional film-former solution can be prepared and optionally dissolved in a solvent. One or more thermal stabilizers can be introduced into the film-former solution. The solution comprising the conductive polymer, if present, can be introduced into the film-former solution. If no film-former is used, the solution comprising one or more thermal stabilizers can be introduced into the solution comprising the conductive polymer (or vice versa). The components can be mixed and coated onto the substrate (or onto the coated substrate). Solvent present in the coating can be removed (e.g., flashed off with heat) before any curing step, if necessary (e.g., if a film-former present requires curing). Any cured coating, if present, can be annealed.

[0175] The coating compositions described herein can be applied onto a coating substrate to form a coating layer by any method known in the coating industry, including, but not limited to, spraying, dripping, dipping, roller, brush or curtain coating, especially spraying.

[0176] The dry thickness of the coating varies depending on the application. In some embodiments, the dry thickness (microns) of the coating layer is less than about 300, 250, 200, 150, 100, 75, 50, 25, 20, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1. The dry thickness can be within the range defined by any two of these values.

[0177] The coating layer provides effective adhesion between the coated substrate and the primer, intermediate, or postcoat layers, if present on the coating. In one example, the coating layer is a primer coating. The coating layer may include additional adhesion promoters as described or exemplified herein.

[0178] Any suitable method known to those skilled in the art can be used to assess the presence or absence of adhesive bonding between a coating layer and another layer (e.g., a coated substrate or a post-coat layer), for example, a cross-hatch test can be used.

[0179] The properties of the coating can be tailored by the type and concentration of the components and / or additional additives. For example, in one example, the final coating can be an antistatic coating. Alternatively, or in addition to antistatic properties, the coating can exhibit one or more additional properties, including, but not limited to, thermal stability, low toxicity, environmental friendliness, good processability, compatibility with coating systems, and / or high stability.

[0180] Purpose Disclosed herein is a method for improving the stability of a conductive polymer coating comprising providing at least one thermal stabilizer to the conductive polymer coating, wherein the thermal stabilizer is selected from an alkali metal salt, an amphoteric metal oxide, an antioxidant, and combinations thereof.

[0181] Also disclosed is the use of one or more compounds selected from alkali metal salts, amphoteric metal oxides, antioxidants, and combinations thereof to improve the thermal stability of a coating, such as a conductive polymer coating.

[0182] In one example, the conductive polymer coating is an antistatic coating.

[0183] In one example, the conductive polymer coating is used at a temperature in the range of about 70°C to about 300°C, about 70°C to about 250°C, about 70°C to about 200°C, about 70°C to about 150°C, about 70°C to about 100°C, about 70°C to about 300°C, about 100°C to about 300°C, about 150°C to about 300°C, about 200°C to about 300°C, about 250°C to about 300°C; or at a temperature of at least about: 70°C, 90°C, 110°C, 130°C, 150°C, 170°C, 190°C, 210°C, 230°C, 250°C, 270°C; or 290°C.

[0184] In another example, the composition or conductive polymer coating is used for electrical de-icing of rotor blades, optionally on fixed-wing aircraft.

[0185] In yet another example, the compositions or conductive polymer coatings are used in radar absorbing, lightning strike protection, energy capture and storage, electromagnetic interference (EMI) shielding, antennas, batteries, capacitors, solar control, and / or anti-corrosion coatings.

[0186] In yet another example, the composition or conductive polymer coating is used to coat wind turbines for power generation.

[0187] Additional Aspects The present disclosure provides, inter alia, the following aspects, each of which may be considered to optionally include any alternative aspects.

[0188] Clause 1. A composition comprising a solution processable polyaniline conductive polymer and one or more thermal stabilizers selected from an alkali metal salt, an amphoteric metal oxide, an antioxidant, or any combination thereof.

[0189] Clause 2. The composition of clause 1, wherein the alkali metal salt comprises a metal selected from one or more of lithium (Li), sodium (Na), potassium (K), beryllium (Be), magnesium (Mg), calcium (Ca), and strontium (Sr), and a counterion of the metal selected from one or more of hydroxide, carbonate, stearate, borosilicate, bicarbonate, metasilicate, phosphate, and hydrogen phosphate.

[0190] Clause 3. The composition of clause 2, wherein the counterion of the metal of the alkali metal salt is selected from carbonate, bicarbonate, phosphate, and hydrogen phosphate.

[0191] Clause 4. The composition of clause 2 or clause 3, wherein the metal of the alkali metal salt is calcium (Ca).

[0192] Clause 5. The composition of any one of clauses 1 to 4, wherein the amphoteric metal oxide is an oxide of zinc, cerium, zirconium, titanium, magnesium, yttrium, aluminum, or silicon.

[0193] Clause 6. The composition of any one of clauses 1 to 5, wherein the amphoteric metal oxide is an oxide of zinc or cerium.

[0194] Clause 7. The composition of any one of clauses 1 to 6, wherein the amphoteric metal oxide is surface treated, optionally with a polymeric dispersant.

[0195] Clause 8. The composition of any one of clauses 1 to 7, comprising an antioxidant which is a hindered phenol.

[0196] Clause 9. The composition of any one of clauses 1 to 8, wherein the one or more antioxidants are selected from pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), n-octadecyl(3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate), ethylene bis(oxyethylene) bis-(3-(5-tert-butyl-4-hydroxy-m-tolyl)-propionate), or combinations thereof.

[0197] Clause 10. The composition of any one of clauses 1 to 9, wherein the one or more antioxidants are selected from bis(2,4-dicumylphenyl)pentaerythritol diphosphate, distearyl pentaerythritol diphosphite, didodecyl 3,3'-thiodipropionate, tris(2,4-ditert-butylphenyl)phosphite, and combinations thereof.

[0198] Clause 11. The composition of any one of clauses 1 to 10, wherein the polyaniline conductive polymer is a conductive polymer sulfonate or a conductive polymer phosphonate.

[0199] Clause 12. The composition of any one of clauses 1 to 11, wherein the conductive polymer is a polyaniline sulfonate.

[0200] Clause 13. The composition of any one of clauses 1 to 12, wherein the polyaniline sulfonate is selected from the group consisting of polyaniline methanesulfonic acid, polyaniline camphorsulfonic acid, polyaniline p-toluenesulfonic acid, polyaniline dodecylbenzenesulfonic acid, polyaniline dinonylnaphthalenesulfonate, and combinations thereof.

[0201] Clause 14. The composition of any one of clauses 1 to 13, wherein the polyaniline sulfonate is polyaniline dinonyl naphthalene sulfonate.

[0202] Clause 15. The composition according to any one of clauses 1 to 14, which is a liquid formulation or a dry film coating.

[0203] Clause 16. The composition of any one of clauses 1 to 15, wherein the total amount of heat stabilizer (wt % of the total composition) is between about 0.1 to about 9, about 0.5 to about 9, or about 1 to about 8.

[0204] Clause 17. The composition of any one of clauses 1 to 16, wherein the amount of conductive polymer (wt % of the total composition) is between about 1 and about 85; about 5 and about 80; about 10 and about 75; or about 15 and about 70.

[0205] Clause 18. The composition of any one of clauses 1 to 17, wherein the amount of conductive polymer (wt % of the total composition) is between about 80 and about 85.

[0206] Clause 19. The composition of any one of clauses 1 to 17, wherein the amount of conductive polymer (by weight of the liquid formulation) is between about 1 and about 85, about 2 and about 80, or about 3 and about 75.

[0207] Clause 20. The composition of any one of clauses 1 to 19, wherein the amount of conductive polymer (by weight % of the dry film composition) is between about 1 to about 85, about 5 to about 80, or about 10 to about 75.

[0208] Clause 21. The composition of clause 1, wherein the heat stabilizer is provided in a particle size of less than about 5 μm.

[0209] Clause 22. The composition of clause 1, wherein the heat stabilizer is provided in a particle size of between about 1 and 100 nm.

[0210] Clause 23. A composition according to any one of clauses 1 to 22, which is a liquid formulation.

[0211] Clause 24. The composition of clause 23, wherein the organic solvent comprises a solvent selected from aromatics, halogenated aromatics, halogenated aliphatic hydrocarbons, aliphatic hydrocarbons, glycols, ethers, glycol ethers, esters, alcohols, ketones, or combinations thereof.

[0212] Clause 25. The composition of clause 23, wherein the organic solvent comprises a hydrocarbon-based solvent, optionally an aromatic hydrocarbon, and optionally toluene, xylene, or a mixture thereof.

[0213] Clause 26. The composition of any one of clauses 23 to 25, wherein one or more of the heat stabilizers present in the liquid formulation are provided as a suspension in the liquid formulation.

[0214] Clause 27. The composition of any one of clauses 1 to 26, comprising at least one film-forming agent.

[0215] Clause 28. The composition of any one of clauses 1 to 27, comprising a film former present in an amount between about 1 and about 20 wt%, about 1 and about 15 wt%, or about 1 and about 10 wt% (wt % of total dry film weight).

[0216] Clause 29. The composition according to clause 39, wherein the film-forming agent comprises a silicone or polysiloxane.

[0217] Clause 30. The composition of any one of clauses 1 to 29, further comprising a dispersant.

[0218] Clause 31. The composition of any one of clauses 1 to 30, in the form of a coating having a resistance of less than about 100 MΩ, about 50 MΩ, about 10 MΩ or about 5 MΩ.

[0219] Clause 32. The composition of any one of clauses 1 to 31, in the form of a coating having a resistance of less than about 100 MΩ, about 50 MΩ, about 10 MΩ or about 5 MΩ at a temperature ranging from about 70°C to about 300°C for at least: about 12 hours, about 24 hours, about 48 hours, about 72 hours, about 96 hours, or about one week.

[0220] Clause 33. A substrate comprising one or more coating layers, at least one of the coating layers comprising a composition according to any one of clauses 1 to 32.

[0221] Clause 34. A coating applied to a substrate which may be coated, (i) the composition according to any one of clauses 1 to 32 Including, a coating.

[0222] Clause 35. A coating according to clause 34, which is an antistatic coating.

[0223] Clause 36. A coating according to clause 34 or clause 35, comprising a polysiloxane.

[0224] Clause 37. The coating of any one of clauses 34 to 36, having a thickness in the range of about 1 to about 10 μm.

[0225] Article 38. (i) a substrate which may be coated; (ii) one or more optional postcoat layers; and (iii) one or more layers located between i) and (ii) comprising the composition according to any one of clauses 1 to 32. 1. A coating system comprising:

[0226] Clause 39. A coating system according to clause 38, which is an antistatic coating.

[0227] Clause 40. A coating according to clause 38 or clause 39, comprising a polysiloxane.

[0228] Clause 41. A coating according to any one of clauses 34 to 37 or a coating system according to any one of clauses 38 to 40, wherein the substrate is selected from a metal, a metal alloy, a polymer, a composite material, carbon fibre, glass fibre or a silicon based material.

[0229] Clause 42. A method for improving the stability of a conductive polymer coating, comprising providing the conductive polymer coating with at least one thermal stabilizer, wherein the thermal stabilizer is selected from an alkali metal salt, an amphoteric metal oxide, an antioxidant, and combinations thereof.

[0230] Clause 43. The method of clause 42, wherein the conductive polymer coating is a composition according to any one of clauses 1 to 32.

[0231] Clause 44. Use of one or more thermal stabilizers selected from alkali metal salts, amphoteric metal oxides, amphoteric metal hydroxides, amphoteric metal minerals or clays, antioxidants, and combinations thereof to improve the thermal stability of a conductive polymer coating.

[0232] Clause 45. The use according to claim 46, wherein the conductive polymer coating is a composition according to any one of clauses 1 to 32.

[0233] Clause 46. Use according to clause 44 or clause 45, wherein the conductive polymer coating is an antistatic coating.

[0234] Clause 47. The use according to any one of clauses 44 to 46, wherein the conductive polymer coating is used at a temperature of at least: about 100°C, about 150°C, about 200°C, about 250°C, or about 300°C.

[0235] Clause 48. The use of any one of clauses 44 to 47, wherein the conductive polymer coating has a resistance of less than about 100 MΩ, about 50 MΩ, about 10 MΩ or about 5 MΩ at a temperature in the range of about 70°C to about 300°C for at least: about 12 hours, about 24 hours, about 48 hours, about 72 hours, about 96 hours, or about 1 week.

[0236] Clause 49. Use according to any one of clauses 44 to 47, wherein the conductive polymer coating is used for electrical de-icing, radar absorption, lightning protection, energy capture and storage, electromagnetic interference (EMI) shielding, antennas, batteries, capacitors, solar control, or anti-corrosion coatings. EXAMPLES

[0237] The present disclosure will now be described with reference to the following non-limiting examples and with reference to the accompanying drawings.

[0238] 1. Preparation of Conductive Polymer A conductive polymer of polyaniline dinonylnaphthalene sulfonate (PANI-DNNSA) was prepared by a continuous flow process to provide a solution of PANI-DNNSA in toluene solution.

[0239] The setup of the continuous controlled flow process for PANI synthesis consisted of two stages. In the first stage, the aniline reagent and protonic acid (A1 and A2 in Figure 1) were mixed at room temperature to form organic stream A3, and then this combined organic stream A3 was mixed with the oxidant stream from B to generate emulsion product stream C in a pressurized zone. This emulsion C was then fed into a temperature-controlled flow reactor D downstream of the pressurized zone, where the reaction was allowed to proceed with active temperature control and reaction monitoring.

[0240] Stage 1: Reagent delivery was accomplished using a three pump configuration (see Figure 1). Pump P-1 was used to deliver aniline solution A1, pump P-2 was used to deliver DNNSA solution A2, and pump P-3 was used to deliver ammonium persulfate solution A3. Both aniline and DNNSA were delivered by Knauer pumps 80P (pumps (P-1 and P-2) can operate at flow rates up to 100 mL / min and pressures up to 400 bar). Pump P-3 is an SSI PR class dual piston positive displacement pump capable of delivering flow rates up to 100 mL / min and pressures up to 276 bar. Reagent streams were transported using PFA tubing (1 / 8” OD, 1 / 16” ID) obtained from VICI and mixed with a SS Swagelok T-piece. Following this initial mixing, the reagents then pass through 15 cm SS tubing (3 / 16” OD, 3.4 mm ID), SM-1, fitted with a PP high shear static mixer (Cambridge Reactor Design). The aniline and DNNSA solution is then combined with the APS solution from P-3 and passes through 30 cm SS tubing (3 / 16” OD, 3.4 mm ID), SM-2, fitted with a PP high shear static mixer (Cambridge Reactor Design). A Swagelok R3A-A pressure relief valve was used to pressurize stage 1. This allows the system pressure to be adjusted in the range of 3.4 to 24.1 bar. All other plumbing of the reactor lines was done using standard Swagelok fittings.

[0241] Stage 2: A 1L shell-and-tube continuous reactor (Cambridge Reactor Design) consists of a series of Hastelloy C276 alloy tubes (8mm OD, 6mm Id) connected in a serpentine fashion within the reactor shell. The reactor is fitted with static mixers along its length and has a total internal volume of 1L. Depending on the auxiliary equipment used, the reactor can be operated over a temperature range of -10°C to 200°C and up to a pressure of 25 bar. In this experiment, reactor temperature control was performed with a Julabo Presto A40 thermostat capable of operation from -40°C to 250°C. Temperature monitoring inside the reactor tube was performed using four PT-100 temperature probes connected at positions 1, 8, 15, and 24 in a 5x5 array that was recorded using an OM-DAQPRO-5300 portable data acquisition and logging system. No back pressure regulator (BPR) was used in this section of the reactor.

[0242] After cooling the 1 L reactor system to 0 °C, aniline (1.0 equiv., neat, 99.5%) was pumped at 0.56 ml / min (P-1) and DNNSA (1.5 equiv., 50% w / w in 2-butoxyethanol) was pumped at 8.71 ml / min (P-2) through Static Mixer 1 (SM-1) for 1 min to form an organic stream. Ammonium persulfate (1.2 equiv., 1.0 M aqueous solution) was then introduced at 7.4 ml / min (P-3). The combined reagent streams were then directed through Static Mixer 2 (SM-2) to form an emulsion product stream, which then entered a pre-cooled 1 L Salamander Jacketed Flow Reactor at a combined flow rate of 16.67 ml / min for a total residence time of 1 h. Steady state product collection was started after 1 h 16 min. After the steady state run was completed, P-3 was switched to a water wash, followed by P-1 and P-2 to toluene. After 3 hours and 28 minutes, collection was stopped and the crude product solution was diluted with toluene (2.45 L). The aqueous layer was then drained and the organics were washed with 0.1 M H2SO4 (3 x 1.25 L) followed by H2O (3 x 1.25 L). The washed organics were then concentrated under reduced pressure and toluene (2.25 L) was added again to azeotrope and further dry the organics. This drying process was repeated once more, after which toluene was added once more to return the solution to the desired concentration (50% w / w).

[0243] A small amount of the PANI-DNNSA concentrate was prepared into a 70% w / v solution in toluene and thin-film cast. The film was dried overnight in an oven at 100°C, then washed with 2-propanol and air-dried. The resulting film had a thickness of 8.25 μm and a conductivity of 10.6 S / cm.

[0244] pyrolysis Various agents were explored to improve the thermal stability of PANI. Using thermogravimetric analysis-mass spectrometry (TGA-MS), it was confirmed that PANI-DNNSA undergoes thermal decomposition over three main stages. First, trapped or adsorbed water is lost from the polymer (35-155°C). Next, DNNSA undergoes desulfonation removing water and sulfur trioxide (155-322°C). At higher temperatures, sulfur trioxide further decomposes to sulfur dioxide. Finally, the PANI backbone begins to decompose losing aniline fragments (322-650°C), with 100% mass loss recorded at temperatures above 650°C. The desulfonation of DNNSA is an equilibrium reaction, whereby the presence of water / dilute acid promotes the desulfonation. Without wishing to be bound by any theory, it is understood that agents including calcium stearate and CaCO3 (Omyacarb 2) may react with both free DNNSA and other acid species formed during decomposition to improve the thermal stability of the conductive polymer. Other agents were also identified that provided improved thermal stability, including Al2O3 (AL-15-25) and Carbosil fumed silica (TS-700).

[0245] The loading of the agent was calculated based on the amount (eq) and weight percent (wt%) of DNNSA in the PANI solution, and was initially set very high to screen whether it had a positive effect on the performance of unmodified PANI.

[0246] Samples were prepared by adding PANI-DNNSA (4.00 g, 35 wt%) in toluene and the desired drug to a vial and stirring overnight at room temperature. Films were then cast from the resulting solution using spin coating and placed directly into a 150 °C oven for the first 0.5 h, which was the reference point for all comparisons of film resistance (Table 1 and Figure 3).

[0247] TIFF2024508584000002.tif51170

[0248] Coatings prepared from solutions 1 and 2 (Table 1) provided transparent films with well-dispersed drug as solid particles, giving a matte appearance without aggregates (see Figure 3). Samples 1 and 2 were transparent with no visible particles to the naked eye, but had a matte appearance compared to the drug-free PANI films. Samples 3, 4, and 5 (amine) reacted immediately with the PANI solution. In each case, the solution was observed to thicken and turn blue to different degrees. When cast, these films contained large polymer aggregates (Error! Reference source not found. 3). Films containing CaCO3 (particle size <2 μm, surface treated) performed very well with stable resistance over a period of 24 hours at 150 °C. The initial drop in resistance was probably due to loss of toluene and reaction of excess DNNSA with CaCO3. After 0.5 hours the film resistance was 2.2 MΩ, whereas after 24 hours at 150 °C the film resistance was 1.5 MΩ, and some darkening of the film was observed. In reference experiments, untreated PANI films generally show a 20-200 fold increase in resistance over 24 hours at 150 °C. Films containing diisopropylamine and diethanolamine also showed good results, despite their poor appearance (Error! Reference source not found. 3). These initial experiments showed that the addition of some agents such as calcium carbonate to PANI-DNNSA could help to further stabilize the conductivity of the polymer over 24 hours, instead of the 4 hours recorded for the unmodified polymer. To further investigate the mechanism of this stabilizing effect, samples containing calcium carbonate agent (O2T) were analyzed by TGA-MS for mass loss and molecular fragmentation changes.

[0249] Samples were prepared as shown in the table below by adding 5 wt% O2T to 40 wt% PANI-DNNSA (Error! Reference source not found. 2, Figures 4 and 5). The samples were then homogenized and cured at 150°C for 30 min in air or under N2. The resulting thin films were then removed from the glass substrate and analyzed by TGA-MS in air or under argon. The TGA-MS was set to heat the samples at 5°C / min for 60 min, followed by holding at 300°C for an additional 4 h.

[0250] TIFF2024508584000003.tif47170

[0251] All samples showed significant mass loss during the dynamic heating cycle (30-300°C) (Figure 5). During the isothermal stage, the mass loss was much less, suggesting that most of the thermal dedoping may be complete by 300°C (Table 2). It was observed that the mass loss upon heating to 300°C was greater for samples cured under N2 (S2 vs. S4, and S3 vs. S5). The electrical conductivity of PANI-DNNSA has previously been shown to be significantly more stable under N2. Therefore, it is believed that the curing step, in which the samples were heated to 150°C for 30 minutes under either air or N2, influenced this result. If the samples were cured under air, it is believed that much of the volatile material had already been lost from the samples prior to analysis by TGA. Conversely, the N2 samples were more stable during curing, and volatiles remained present in the samples. When exposed to high temperatures in air, the N2 samples lost more material than the air samples, resulting in the results shown above. Essentially, the N2 samples had lost more mass at the start of the test. The samples with O2T lost much less mass than those without O2T (S1 vs. S2). The dynamic mass change of S1 was 62 wt%, whereas S2 showed only a 43 wt% mass change at the same temperature. S2 was also a bit more stable during isothermal heating (10 wt% vs. 14 wt%). This supports our hypothesis based on the conductivity observations that O2T reduces the thermal decomposition of PANI-DNNSA. While the TGA data supports the finding that O2T retards desulfonation or stabilizes PANI by another mechanism, further support was provided by the MS data. All samples underwent significant mass loss between 150-300 °C. The largest mass loss was H2O, followed by SO2 (m / z 64), SO (m / z 48), and SO3 (m / z 80). All of these species have been linked to the thermal desulfonation of DNNSA (Error! Reference not found. 6).

[0252] All samples, including S3 and S5, showed two clear water signals. The first occurs between T = 30-150 °C, peaking at T = 50 °C. This is believed to be due to the removal of water adsorbed on the polymer (Error! Reference source not found. 7). The second occurs between T = 175-300 °C, peaking at T = 250 °C. This is believed to be due to the desulfonation of DNNSA and the reaction of excess acid with CaCO3 in the samples containing O2T. The second peak is consistent with most of the other peaks, including the loss of SO2, SO, and SO3.

[0253] The TGA-MS data demonstrate that oxidation, alongside thermal dedoping, plays a role in the degradation of PANI. To evaluate the effect of oxidation on the conductivity of PANI, samples containing various amounts of OT were placed in a vacuum oven, which was purged with N2 before being heated to 150 °C. While the film resistance increased rapidly after 24 h in air, the resistance remained stable under N2 for over 5 days (Figure 8).

[0254] Fresh batches of samples prepared with various levels of O2T were prepared and heated at 150 °C under N2 for up to 7.9 days, with no loss in performance for films with >5 wt% O2T. This indicates that O2T can stabilize PANI against acid degradation, but oxygen also plays a significant role in attacking the PANI backbone and ultimately losing electrical performance. After 7.9 days under nitrogen, the same films with varying concentrations of O2T were heated at 150 °C in the presence of air for an additional 6.8 days. Here, these films were observed to be relatively stable for up to 3 days before an increase in resistance was measured. The increased stability for films placed directly in an oxidizing environment may suggest that fully curing the film can provide some protection against oxidation. With increasing O2T concentration, film stability increased up to 10 wt% loading. Nominal differences were observed between the 10 wt% and 15 wt% samples. Observations of PANI films also point to the stabilizing effect of O2T. The 10 wt% and 15 wt% samples did not darken as quickly as films with lower O2T loadings. The 1-5 wt% films generally darkened and cracked after 80 h at 150 °C. The effect of oxygen on PANI-O2T films was further investigated by preparing new films with 5 wt% O2T loading, which were then cured and heated under N2 (Figure 9). The sample cured under N2 showed good thermal stability, but only a small increase in resistance over a 7 day period (initially 4.5 x 10 5 Ω: 6.0 x 10 5 Ω).

[0255] It is understood that both CaCO3 and ZnO react with free DNNSA to form the respective Ca and Zn salts. To better understand the stoichiometry required and how it relates to the observed film failure times, the concentrations of CaCO3(O1) and ZnO were converted from weight percent to molar equivalents. The amount of free DNNSA was calculated based on the amount expected in a 35 wt% PANI solution. Based on the XPS data for 10 untreated films, there is an average of 1.37 eq of DNNSA present relative to the aniline, with 0.491 eq bound to the emeraldine salt polymer (Table 3).

[0256] TIFF2024508584000004.tif48170

[0257] Based on previous data obtained for various loadings of CaCO3, loadings above 1.40eq (5wt%) significantly increased the failure time. At loadings below 0.54eq (2wt%), the membranes performed very poorly. Results for formulations containing ZnO showed short failure times at loadings below 0.67eq (2wt%) and longer failure times at loadings above 0.67eq up to 1.73eq (5wt%). Although excessively high loadings of ZnO may have adverse effects, the benefits appear to continue beyond those seen at 1.73eq. The observed difference in behavior between CaCO3 and ZnO may be due to the fact that CaCO3 is an alkali salt while ZnO is an amphoteric oxide. This may be due to reactivity, solubility, or both.

[0258] 2. Preparation of Heat-stabilized Conductive Polymer Coatings Various agents were further investigated to slow down the desulfonation of the DNNSA dopant and prevent side reactions of the degradation by-products with the PANI backbone. Formulations with varying concentrations and agents were prepared using the Chemspeed robotic system. Powder or liquid agents with varying weight percentages relative to PANI-DNNSA were manually weighed into each vial and then automatically filled with 4.0 grams of PANI solution (41 wt%) using the viscous liquid gravimetric dispensing unit tool of the Chemspeed robot. The resulting solution was then homogenized for 3 minutes using a 12 mm diameter homogenizer tool in the Chemspeed robot (dial setting 30). The coating formulation was then poured into a 2.5 cm 2 The samples were spin-coated (40 s @ 2000 rpm) onto glass slides within 3 h and dried in an oven at 150 °C for 30 min. The resistance of each sample was then recorded over time using a custom-designed continuous measurement device that can withstand a temperature of 150 °C.

[0259] The drugs investigated in this further study are listed below. 1.O2T-Omyacarb 2 (CaCO3) 2.DEA - Diethanolamine 3.DIPA - Diisopropanolamine 4. SA-Succinic acid 5. CBS - Sodium Bisulfite 6. Ci-Carbon Filler (Intelliparticle 7284) 7. Cg-Carbon Filler (CSIRO) 8. Al-15-25 - Aluminum oxide (15-25 nm)

[0260] The appearance of the thin films varied greatly depending on the agent used. PANI films containing DEA and DIPA showed large particle aggregation, and the solutions became very viscous with a mixture of liquid and sludgy components as the concentration increased. Based on these observations, this class of amine agents was found to be unsuitable. Films containing carbon filler (Ci) were homogeneous, but particles were visible on the surface when the concentration was increased from 1 wt% to 10 wt% for the PANI-DNNSA solution. All samples (except O2T) showed a significant increase in resistance after 24 hours at 150 °C. The performance of the amines (DEA and DIPA) was poor and they were not considered for the PANI formulation. Particularly effective was found to be calcium carbonate (O2T). Concentrations of O2T were examined from 1 to 15 wt%. Samples with 5, 10, and 15 wt% were found to provide particularly effective and stable resistance over 24 hours at 150 °C.

[0261] A series of different agents to prevent thermal degradation of PANI were also investigated (Table 4 and Figure 10). Samples were prepared by weighing 4 g of PANI-DNNSA (41 wt%) into a glass vial and adding various amounts of each agent. The resulting solutions were mixed using a vortex stirrer and stirred at 2.5 cm for 40 s with the following parameters: 2000 rpm, 40 s. 2 The samples were spin-coated onto a glass slide and then cured in an oven at 150°C for 30 minutes. The resistance of each sample was then measured using a multiplate conductivity reader. The sample was judged to have broken down when the resistance exceeded 100 MΩ, which was the time to break down (h).

[0262] TIFF2024508584000005.tif107170

[0263] Particularly effective agents were found to be calcium borosilicate CW-291 (Halox), Micronisers nano zinc oxide, and various calcium carbonates, especially Omyacarb 1. With these agents, the failure time was extended to 95 hours (~4 days), whereas unmodified PANI was only stable for 4.5 hours. Note that unmodified PANI started at a high resistance (11.9 MΩ) whereas O1 (5 wt%) started at 0.3 MΩ.

[0264] 3. Preparation of Heat-stabilized Conductive Polymer Coatings Silicone Coating Compatibility and Screening A series of formulations were prepared to test the solubility of PANI-DNNSA in various silicone-based coatings for high temperature applications: 1. RTV silicone dispersion coating (Nusil, R-1009, 1-pack system) 2. Low viscosity, thermally conductive silicone (Nusil, R-2939, 2-pack system, 1:1 ratio) 3. RFI and EMI shielding RTV silicone elastomer (Nusil, R-2631, 2-pack system, 15:1 ratio) 4. Ice phobic coating (Nusil, R-2180).

[0265] Test formulations were prepared with each silicone according to the following general procedure. For R-2631, equal amounts of Part A (5 g) and Part B (5 g) were weighed into a glass bottle and mixed thoroughly. Toluene was then added gradually to check solubility, but the mixture remained thick and viscous and was not used for spin coating. R-2939 was mixed thoroughly with Part A (3 g) and Part B (0.2 g) in a 15:1 ratio before the PANI-DNNSA was added. Some phase separation occurred as a result. Formulations containing the silicone coating (R-2180) showed short failure times and generally high initial film resistance. The recommended cure schedule for R-2180 is 30 min at room temperature, then 45 min at 75°C, and finally 135 min at 150°C. This cure schedule proved to be too harsh for PANI without the thermal stabilizer. Therefore, a modified cure schedule was used, heating at 75°C for 1 h, then 50°C for 17 h, and finally 150°C for 30 min. The samples were equilibrated at room temperature for 5 hours and then placed in an oven. Initial film resistance was high and, as a result, failure times tended to be short (~5 hours) even without the addition of stabilizers. This silicone formulation is preferred at lower loadings, but may still be useful if mechanical properties require more silicone relative to PANI. Next, compatibility of PANI with silicone R-1009 was tested at silicone concentrations from 1 to 15 wt%. Samples up to 10 wt% formed homogeneous solutions, while the 15 wt% sample showed some phase separation. The PANI-silicone samples were then placed in a 150°C oven and the conductivity was monitored over time. A multiplate conductivity logger can read a maximum resistance value of ~100 MΩ. This value was selected as the failure point of the film and was confirmed using an offline multimeter. See Figure 12 for samples S1 to S5, which provides continuous logging of film resistance for samples containing different amounts of silicone dispersion (R-1009).

[0266] There was little difference in failure time between the different silicone loadings. Based on this result, a loading of 10 wt% was chosen to maximize silicone loading while avoiding the phase separation seen at higher loadings.

[0267] Although CaCO3 and ZnO have been shown to be effective thermal stabilizers that reduce the thermal degradation of PANI, oxidation of the polymer backbone remains. To address this process, a series of experiments were conducted investigating antioxidants. These agents were generally considered to be primary or secondary depending on their mechanism of action. Primary antioxidants such as hindered phenols (e.g., Irganox 1010 and Irganox 1076) can act as radical scavengers that scavenge peroxy radicals. Ultimately, the primary antioxidants are sacrificial and when completely consumed, polymer degradation begins. Secondary antioxidants work by scavenging organic peroxides that are formed by the action of the primary antioxidants. These can be phosphites, but thioethers can also be used and can be effective in preventing long-term heat aging. Several formulations were prepared from PANI-DNNSA (4.0 g), R-1009 (10 wt%), and O2 (5 wt%) along with antioxidants, as listed in Table 5 below. The resulting solution was stirred for 5 days, then spin-coated onto a glass slide and cured at 60 °C and 70% RH. The film was green, transparent, shiny, and free of visible particles. The sample was considered to have failed when the resistance exceeded 100 MΩ, which was the time to failure (h).

[0268] TIFF2024508584000006.tif57170

[0269] All samples containing Irganox performed significantly better than the non-containing samples (5 wt% O2 without Irganox = 55.6 hours). The Irganox samples lasted up to 103 hours. Samples A and B performed better than C and D, suggesting that 5 wt% silicone in the dry film is superior to 10 wt% silicone in the dry film. No significant difference was observed between 0.5 wt% and 1.0 wt% Irganox loadings.

[0270] A series of different ZnO concentrations were also investigated in the PANI-DNNSA formulation. Samples were prepared from PANI-DNNSA (35 wt%). Samples with 0, 0.1, 0.5, 1, 2, and 5 wt% ZnO loadings showed increased thermal stability, especially above 2 wt% loading (Figure 11). The failure time for the sample containing PANI was 10.8 hours. This increased to 12.8 hours with the addition of 10 wt% silicone (R-1009). Increasing the amount of ZnO then significantly improved the thermal stability, extending the failure time to 96.7 hours at 5 wt% loading. It was found that the performance of the two different Irganox agents differed when ZnO was used. Irganox 1010 performed better than Irganox 1076 and significantly better than ZnO alone as shown in the results below: ZnO 1wt% = 28.2 hours failure time ZnO 1wt% + Irganox 1076 1wt% = 67.2 hours failure time · 1wt% ZnO + 1wt% Irganox 1010 = 79.2 hours failure time.

[0271] O1 (5 wt%) showed a slight improvement in failure time compared to no additive (failure time = 20.5 h). The combination of O1 and Irganox 1076 showed good performance (failure time = 92.5 h) compared to only 67.0 h for Irganox 1010.

[0272] The description of various aspects of the present disclosure is presented for illustrative purposes and is not intended to be exhaustive or limited to the disclosed aspects. Numerous modifications and variations that do not depart from the scope of the described aspects will be apparent to those skilled in the art. The terms used in this specification are selected, for example, to best explain the principles of the aspects, practical applications or technical improvements of the technology found in the market, or to make the aspects disclosed herein understandable to others skilled in the art.

Claims

1. 1. A liquid formulation comprising: a solution processable polyaniline conductive polymer in an organic solvent; a first heat stabilizer selected from the group consisting of alkali metal salts, amphoteric metal oxides, or combinations thereof; a second heat stabilizer selected from one or more antioxidants; Including, the first heat stabilizer is about 2 wt % to about 7 wt % of the formulation; the total amount of the first heat stabilizer and the second heat stabilizer is less than about 9 wt % of the formulation; the first heat stabilizer and the second heat stabilizer are present in an organic solvent; the polyaniline conductive polymer solution having greater than 95% polyaniline salt dissolved in the organic solvent; liquid formulation.

2. 10. The liquid formulation of claim 1 further comprising one or more film forming agents.

3. The liquid formulation of claim 1, wherein the alkali metal salt comprises a metal selected from one or more of lithium (Li), sodium (Na), potassium (K), beryllium (Be), magnesium (Mg), calcium (Ca), and strontium (Sr), and a metal counterion selected from one or more of hydroxide, carbonate, stearate, borosilicate, bicarbonate, metasilicate, phosphate, and hydrogen phosphate.

4. 4. The liquid formulation of claim 3, wherein the counterion of the metal of the alkali metal salt is selected from carbonate, bicarbonate, phosphate, and hydrogen phosphate.

5. The liquid formulation of claim 3, wherein the metal of the alkali metal salt is calcium (Ca).

6. The liquid formulation of claim 1, wherein the alkali metal has an average particle size of less than about 2 μm.

7. The liquid formulation of claim 1, wherein the amphoteric metal oxide is an oxide of zinc, zirconium, titanium, magnesium, yttrium, aluminum, or silicon.

8. The liquid formulation of claim 1, wherein the amphoteric metal oxide is an oxide of zinc.

9. The liquid formulation of claim 1, wherein the amphoteric metal oxide is surface treated.

10. The liquid formulation of claim 9, wherein the amphoteric metal oxide is surface treated with a polymeric dispersant.

11. The liquid formulation of claim 1, wherein the amphoteric metal oxide comprises less than about 3 wt. % of the liquid formulation.

12. The liquid formulation of claim 1, wherein the second thermal stabilizer comprises between about 0.5 wt % and about 3 wt % of the liquid formulation.

13. The formulation of claim 1, wherein the antioxidant is selected from one or more hindered phenols.

14. The liquid formulation of claim 1, wherein the one or more antioxidants are selected from the group consisting of pentaerythritol tetrakis (3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), n-octadecyl (3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate), ethylene bis(oxyethylene) bis-(3-(5-tert-butyl-4-hydroxy-m-tolyl)-propionate), or combinations thereof.

15. The liquid formulation of claim 1, wherein the one or more antioxidants are selected from the group consisting of bis(2,4-dicumylphenyl)pentaerythritol diphosphate, distearyl pentaerythritol diphosphite, didodecyl 3,3'-thiodipropionate, tris(2,4-ditert-butylphenyl)phosphite, and combinations thereof.

16. The liquid formulation of claim 1, wherein the polyaniline conductive polymer is an organic solvent soluble polyaniline conductive polymer salt prepared in situ by polymerizing aniline monomers with a protonic acid.

17. The liquid formulation of claim 1, wherein the polyaniline conductive polymer is a polyaniline sulfonate.

18. The liquid formulation of claim 1, wherein the polyaniline conductive polymer is selected from the group consisting of polyaniline methanesulfonic acid, polyaniline camphorsulfonic acid, polyaniline p-toluenesulfonic acid, polyaniline dodecylbenzenesulfonic acid, polyaniline dinonylnaphthalenesulfonic acid, and combinations thereof.

19. The liquid formulation of claim 1, wherein the polyaniline conductive polymer is polyaniline dinonyl naphthalene sulfonate.

20. The liquid formulation of claim 1, wherein the liquid formulation is a dry film coating.

21. The liquid formulation of claim 1, wherein the polyaniline conductive polymer comprises between about 80 wt % and about 90 wt % of the liquid formulation.